Pengaruh Motivasi Kerja Dan Kompensasi Terhadap Kinerja Karyawan Dengan Masa Kerja Sebagai Variabel Moderating Studi Pada Rumah Sakit Umum Muhammadiyah Metro - Finka Wulandari; Jati Imantoro; Slamet Tedy Siswoyo (Jurnal Manajemen DIVERSIFIKASI, 2024)
Based on attendance data for Muhammadiyah Metro General Hospital employees in December 2022, medical employees have the lowest percentage value, with an average of 55% of the number of days, the number of delays, and the number of early discharges. Based on these data, hospitals need to increase work motivation in employees in order to reduce the number of delays in entering employee work. The purpose of this study is to find out whether work motivation and compensation affect employee performance. To find out whether the length of service is able to moderate the effect of work motivation and compensation on employee performance. This study is a descriptive quantitative study with a sample of 81 employees. Data collection using questionnaires and data analysis using validity tests, reliability tests, normality tests, linearity tests, homogeneity tests, multiple regression analysis tests, t tests, r2 determination tests, and MRA tests using programs (SPSS). The results showed that work motivation had an effect and positively on employee performance. Job satisfaction has an effect and is positive on performance. Length of service affects the relationship between work motivation variables and employee performance variables. Length of service affects the relationship between job satisfaction variables and employee performance variables.